Green approaches of Malaysian green hotels and resorts - Yusof, Zeenat Begam; Jamaludin, Mariam (Elsevier, 2013)
Currently tourism is moving towards sustainable tourism because this industry poses negative impacts on the environment. Tourism industry consumes and produces many resources such as water, energy and waste. The purpose of this research is to determine the rate of participation in green approaches of Malaysia green hospitality industry. The methodology used was in depth interviews and observations. This research finding shows that the operators adopt greener approaches in three common areas such as energy, waste and water. Less participation in indoor air quality, sustainable management of the site, renewable energy and rainwater harvesting system.